Indian Woman, Trinidad - No. 5 - (:unkn) unknown (My University, 2008)
A portrait of a woman of East Indian origin wearing traditional Hindu garments: sari, choli and a skirt. She is adorned with a nose ring, bangles on her wrists, armlets on both arms, a mang tikka in her hair, earrings and necklaces. The postcard includes a Trinidad and Tobago one cent stamp dated February 24th, 1931.
Colour: Brown and White; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Women, East Indian--Trinidad and Tobago; 1931; Trinidad and Tobago; Saris--India; Nose rings--India; East Indians--Trinidad and Tobago; Ethnic costume--India; Bracelets--India; Armbands--India; Necklaces--India; Earrings--India; Hair ornaments--India; Clothing and dress--Trinidad and Tobago; Women's clothing--Trinidad and Tobago